Increased Leg Power of Female Fighters through Plyometrics Double Leg Lateral Hop Exercise: An Experimental Study - Samudiyanto, Arief; Subekti, Nur; Fatoni, Muhad (Universitas Muhammadiyah Surakarta, 2023)
This investigation aims to determine whether the Plyometric Double Leg Lateral Hop Exercise enhances leg power in female martial artists. Twenty female martial artists from the Perguruan Tapak Suci Putera Muhammadiyah in the Boyolali District, constituting twenty athletes, were the focal point of this inquiry. As outlined by Hamilton et al. (2008), the Triple Hop Jump Test was utilised to gauge the power capacity of the leg muscles as part of the data collection methodology. According to the reference cited from id.scribd.com/document, the athlete stands on the leg under evaluation and then leaps forward as far as possible, commensurate with their ability. This assessment tool serves to evaluate dynamic stability using a single forward jump. The data analysis method employed in this study involved a t-test using SPSS version 25, with significance testing for differences. The study's outcomes reveal that the Plyometric Double Leg Lateral Hop Exercise contributes to increased limb power among female martial artists. Nonetheless, given that the study's cohort and sample exclusively comprise female combatants, prudence is advised in extrapolating the findings to broader training paradigms. Subsequent investigations should consider the specific physiological attributes that influence the performance of martial arts athletes.